Community Welfare Perspective Islamic Human Development Index (IHDI) - Yunadi, Ahmad; Hanafi, Syafiq Mahmadah; Muslim, Aziz (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study aims to analyze community welfare through the Islamic Human Development Index (IHDI) frameworkDesign/methodology: Utilizing a Comprehensive Literature Review (CLR) approach, the research examines previous studies indexed in Scopus and Emerald, selecting three relevant articles that explore community welfare from the IHDI perspectiveFindings: The IHDI framework is based on five maqasid sharia: ad-Din (religion), an-Nafs (life), al-Aql (education), an-Nasl (family), and al-Mal (wealth). Thus, well-being is assessed through both material (M) and non-material (NM) dimensions. IHDI and HDI have a positive correlation, therefore IHDI can serve as a predictive measure for HDI rankings, the advantages of IHDI are more comprehensive and holistic in measuring community welfare.Practical implications: The Islamic Human Development Index (HDI) can be calculated to quantify human well-being in Islam.Originality/Value: There is no literature review that specifically discusses the concept of IHDI from several previous authors.